The money market sensitivity on the stock market / Wan Mansor Wan Mahmood and Zetty Zahureen Mohd Yusoff - Wan Mahmood, Wan Mansor; Mohd Yusoff, Zetty Zahureen (Institute of Research, Development and Commercialization (IRDC), 2006)
This paper employs the cointegration tests and error correction model to investigate the impact ofeasing money market on stock returns in Malaysia following the Asian financial crisis during 1997 to 2000. The monthly data on Kuala Lumpur Interbank Offer Rates (KLIBOR), the monthly closing of Kuala Lumpur Composite Index (KLCI) andthe sector indexes - construction, consumer product, finance, industrial product, plantation, properties, mining, andtrading andservices, from January I, 1997 to December 31,2000 are used. The results suggest that there is long-term relationship between KLlBOR andsub sample 2, KLlBOR and constructions, KLlBOR and properties, and KLlBOR and mining.